PENGARUH ASIMETRI INFORMASI, PERENCANAAN PAJAK, KOMPENSASI MANAJEMEN, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia periode 2012-2016) - Khairini, Renny; Taufik, Taufeni; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The purpose of this research is to know influence of asymmetry information, tax planning, management compensation, profitability and size of company to earnings management at mining company listed in Indonesia Stock Exchange (BEI) year 2012-2016. The population of this research is mining companies listed in Indonesia Stock Exchange (BEI) in 2012-2016 as many as 70 companies. The sample is chosen by purposive sampling method. Through the criteria applied, selected samples of 14 mining companies. The analytical method used is multiple linear regression analysis. The result of research shows that the variable of information asymmetry and firm size have no effect to earnings management, while variable of tax planning, management compensation, and profitability have an effect on earnings management in sample company. The result of adjusted R Square of 0.127 means that the influence of independent variables (asymmetry information, tax planning, management compensation, profitability and size of company) to the dependent variable (earnings management) is 12.7% while the remaining 87.3% is influenced by other variables not included in this study.Keywords : Earnings management, asymmetry information, tax planning, management compensation, profitability and size of company